The impact of intellectual property rights and the level of information sensitivity on information security in the United Arab Emirates - Shwedeh, Fanar; Yas, Nadia; Abdijabar, Zeana; Flayyih, Najlaa; Fadli, Ahmad; Yas, Harith; Allouzi, Adel Salem (Journal of Infrastructure, Policy and Development, 2024)
In the rapidly evolving landscape of technological innovation, the safeguarding of Intellectual Property Rights (IPR) emerges as a critical factor influencing economic growth and technological advancement. This study, conducted in the context of organizations operating in the United Arab Emirates (UAE), meticulously explores the intricate dynamics between IPR awareness, enforcement, and their implications for information security practices. The research undertakes a thorough investigation with three primary objectives: a comprehensive examination of IPR awareness, an exploration of the relationship between IPR enforcement and information security practices, and an assessment of the impact of information sensitivity. To achieve these objectives, a sample population of 150 respondents from various sectors was engaged, employing a combination of survey instruments and robust statistical analyses. The findings of the study illuminate a strong positive correlation between IPR awareness and information security practices, underscoring the pivotal role of cultivating IPR awareness among organizations. Furthermore, the enforcement of IPR, intricately connected with a resilient legal framework, regulatory authorities, international agreements, and effective customs and border control measures, is identified as a significant influencer of information security practices. The study employs a statistical model that exhibits a high explanatory power, elucidating approximately 85.9% of the variance in information security practices. In conclusion, the research offers profound implications for organizations, policymakers, and stakeholders in the UAE, advocating for strategies such as education, legal and regulatory support, international collaboration, and robust access control mechanisms to fortify IPR awareness, enforcement, and information security practices. The integration of advanced tools such as the smart PLS software adds depth and reliability to the study’s analytical framework, contributing to its comprehensive insights.